The Augustine-Braude Bigelow Survival Debate: A Postmortem and Prospects for Future Directions - Sudduth, Michael (Journal of Scientific Exploration, 2024)
In 2021, the Bigelow Institute for Consciousness Studies (hereafter, BICS) sponsored an essay competition designed to solicit the best evidence for the hypothesis that human consciousness survives bodily death, and more specifically, evidence that would prove this hypothesis beyond a reasonable doubt. The summer 2022 issue of the Journal of Scientific Exploration featured a special subsection on the BICS contest and its winning essays. Robert Bigelow and Colm Kelleher outlined the motivation, design, and judging criteria for the competition. Keith Augustine provided an extensive critical commentary on the contest design and eight of its prominent winning essays. Stephen Braude and several coauthors1 responded to Augustine’s criticisms, and Augustine provided a reply to Braude and his collaborators. Finally, the subsection concluded with a collaborative paper in which Etienne LeBel, Adam Rock, and Keith Augustine proposed a more rigorous experimental design for testing the survival hypothesis.